The Cone Beam O-Arm Imaging System: Radiation Dose, Image Quality, and Clinical Applications - Zhang, Jie (Recent Patents on Medical Imaging (Discontinued), 2013)
The O-armTM Imaging System (O-arm) is a patented x-ray imaging apparatus with a generally O-shaped gantry ring. It combines a traditional C-arm fluoroscope in a two-dimensional (2D) scan acquisition mode and a computed tomography (CT) scanner in a three-dimensional (3D) scan acquisition mode. Although the O-arm was originally designed primarily to support orthopedic surgery, it also has a potential for image-guided surgery and vascular surgery. Since its introduction in 2006, the O-arm cone beam imaging system has gradually gained acceptance and applications in both orthopedic and radiology departments. This paper provides an overview of patient radiation dose, image quality, as well as clinical applications of the O-arm cone beam imaging system.
Keywords: orthopedic surgery